2004
DOI: 10.1007/s00774-004-0522-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of effectiveness of oral administration of collagen peptide on bone metabolism in growing and mature rats

Abstract: The purpose of this study was to examine the effectiveness of collagen peptide intake on bone metabolism in growing (G) and calcium-deficient mature (M) rats. As for the dosages used, they were amounts equal to the recommended supplements for humans (0.166 g/kg body weight (BW) per day: Coll-1G and Coll-1M groups), 10-fold higher (1.66 g/kg BW per day: Coll-10G and Coll-10M groups), and 100-fold higher (16.6 g/kg BW per day: Coll-100G group). In growing male rats, bone mineral density (BMD) of the femur in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
99
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 18 publications
3
99
1
3
Order By: Relevance
“…Oliveira et al (2001) reported that TG, but not TC, decreased significantly when mice were fed a 10% casein + 10% gelatin diet, compared with a 20% casein diet. Similar results were obtained when rats were fed a diet containing 0.166 g/kg body weight CP (Wu et al, 2004) or 0.17% CP (Saito et al, 2009). In contrast, blood TC levels were lower in rabbits fed a 12% casein + 8% gelatin diet than in rabbits fed TESTWako, respectively; Wako Pure Chemicals Co., Osaka, Japan).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Oliveira et al (2001) reported that TG, but not TC, decreased significantly when mice were fed a 10% casein + 10% gelatin diet, compared with a 20% casein diet. Similar results were obtained when rats were fed a diet containing 0.166 g/kg body weight CP (Wu et al, 2004) or 0.17% CP (Saito et al, 2009). In contrast, blood TC levels were lower in rabbits fed a 12% casein + 8% gelatin diet than in rabbits fed TESTWako, respectively; Wako Pure Chemicals Co., Osaka, Japan).…”
Section: Introductionsupporting
confidence: 67%
“…In addition to their use as amino acid sources for protein synthesis in the body, ingested gelatin or CP affects various body functions. For example, gelatin ingestion results in increased bone mineral density and bone strength (Koyama et al, 2001;Wu et al, 2004). Meanwhile, CP supplementation increases the diameter and density of collagen fibrils, the major components of the dermis and tendons (Minaguchi et al, 2005;Matsuda et al, 2006), and the effects of CP are superior to those of lactalbumin for increasing bone mineral density (Koyama et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al (2004) reported that the ingestion of CP at a dose higher than 0.166 g/kg body weight for 4 weeks resulted in a significantly lower concentration of plasma triacylglycerides in rats. Saito et al (2009) reported that the ingestion of 0.4 g CP in combination with 0.5 mL soybean oil induced significantly lower serum triacylglyceride levels 2 h after ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Brittle nails are improved (Rosenburg et al, 1957), and hair diameter increases following the ingestion of gelatin (Scala et al, 1976). In addition, it was reported recently that serum triacylglycerides are decreased following ingestion of CP (Wu et al, 2004;Saito et al, 2009), suggesting the possibility that ingested CP modulates lipid metabolism by altering the function of the liver and/or adipocytes.…”
Section: Introductionmentioning
confidence: 99%